UTILIZATION OF BENGKOK LAND AS CULTIVATED LAND AFTER THE ENFORCEMENT OF KUDUS REGENT REGULATION 62/2023 - Yusrul Hana (Universitas Negeri Semarang, 2026)
The utilization of bengkok land in Undaan Tengah Village is regulated under Kudus Regent Regulation No. 62 of 2023, which requires village asset management to be further stipulated through Village Regulations. However, in practice, the village has not yet established a specific Village Regulation governing the utilization of bengkok land as agricultural land. This study aims to analyze the implementation of bengkok land utilization and identify the legal and practical obstacles arising from the absence of such regulation. This research employs a juridical-empirical method with a descriptive qualitative approach. Data were collected through interviews with the Village Head, Village Consultative Body, village officials, auction committee members, and community participants involved in bengkok land management, supported by relevant legal documents and literature. The findings show that bengkok land is utilized through an annual auction system; however, the absence of a Village Regulation results in weak legal certainty. Problems include defaults by auction winners, re-auctions, delays in planting seasons, and reduced economic efficiency. The study concludes that establishing a Village Regulation is important to ensure legal certainty, clarify rights and obligations, prevent defaults, and optimize land utilization.